Porovnání vlastností alternativních pelet - Jansa, Oldřich (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2011)
Diplomová práce se svým obsahem zabývá alternativními peletami a jejich výrobní cestou od suroviny až po expedici konečnému zákazníkovi. Teoretická část obsahuje popisy metod a používaných technologií výroby. Dále práce obsahuje nástin České a Evropské legislativy v oblasti topných pelet. Praktická část se zabývá měřením a porovnání normalizovaných vlastností vybraných pelet.

This thesis deals with the alternative pellets and the means of production from raw material to final customer. The theoretical part deals with different techniques and manufacturing technologies used. Furthermore, the work deals with Czech and European legislation in the field of fuel pellets. The practical part deals with measuring and comparing the properties of selected standard pellets.
Comparison of properties of alternative pellets
Keywords: pelety; alternativní; legislativa; spalné teplo; vlhkost; obsah popela; sypná hmotnost; pellets; alternative; legislation; combustion heat; moisture; ash content; bulk density